The attitudes and cultural norms of Hong Kong's medical students toward online education: a comprehensive study. - SAI HENG , SAI HENG; DR SURIYAKALA , DR SURIYAKALA; DR FARRA AIDAH BINTI JUMUDDIN , DR FARRA AIDAH BINTI JUMUDDIN (International Journal of Multidisciplinary Research and Studies, 2024)
It is recommended that this study investigate how medical students in Hong Kong feel about using online courses. Several online education pilot programmes were set to begin, while others were in the planning stages. There are a number of other schools that have adopted a similar policy, so this is a good opportunity to hear students' thoughts. To get high-validity insight into students' practices, this research presents an exploratory mixed-methods approach to examining the aforementioned challenges. The research may be seen as having two parts: the first involves qualitative ethnographic fieldwork, while the second involves a quantitative questionnaire (Greene et al., 1989). The purpose of this collaborative research was to present a detailed portrait of how medical students feel about and approach online education. The purpose of this mixed-methods approach was to take the most useful aspects of each phase and use them together to get insight into a previously unexplained phenomenon. Triangulating the findings might be useful because we have both qualitative and quantitative data to consider.